A complete computer aided engineering (CAE) modelling and optimization of high pressure die casting (HPDC) process. (December 2020) - Dou, K.; Lordan, E.; Zhang, Y.J.; Jacot, A.; Fan, Z.Y.
Highlights: The entire HPDC process are chained in the simulation platform and validated against experiments. The optimum casting condition are determined from modelling and experiments aspects. The castings with improved mechanical properties are produced based on previous research results. Abstract: The application of computer aided engineering (CAE) has become a trend in manufacture industry due to its great efficiency and reliability. In casting industries, numerical modelling of the casting process based on CAE has replaced traditional trial-and-error R&D procedures in many aspects. With advanced parallel computing techniques and numerous calculation models, the fluid flow, heat transfer, solidification and defect formation behaviours under different casting conditions may be examined in detail. Based on this idea, component design and the optimization of casting parameters may be carried out to produce products for subsequent microstructural and mechanical characterization. In this way, a direct link between process condition, casting quality, and cast mechanical properties may be established in a manner that is practical, economical and energy efficient for such processes as gravity die casting, high pressure die casting (HPDC) and continuous casting. In this work, the entire HPDC process, including die heating, thermal die cycling, shot sleeve pre-filling, slow shot/fast shot injection, die filling/solidification as well as intensification, is simulated for an Al-Si alloy using the casting simulation package ProCAST. The interfacial heat transfer coefficients between melt and die wall/shot sleeve are adjusted according to thermal couple measurements and infrared imaging of the die surface temperature distribution. Based on this complete numerical model, the HPDC process may be optimized using the following methodology: 1) the optimum thermal die cycle number is determined after which the dynamic steady state of die temperature is obtained to guarantee relatively sound casting quality. 2) The piston shot profile is adjusted to reduce defect formation during injection. In the meantime, tensile bars are cast using the optimized piston shot profile and the mechanical properties (yield strength, ultimate tensile strength and elongation) are tested to assess the effectiveness of the computer simulation. Results show that the mechanical properties are improved with the optimized process parameters, providing further evidence that CAE could help in the optimization of HPDC processes.